Data from: Seasonal movements of Gyrfalcons Falco rusticolus include extensive periods at sea [Maniitsoq] ... - Burnham, Kurt K. (Movebank Data Repository, 2020)
Little information exists on the movements of Gyrfalcons Falco rusticolus outside the breeding season, particularly amongst High Arctic populations, with almost all current knowledge based on Low Arctic populations. This study is the first to provide data on summer and winter ranges and migration distances. We highlight a behaviour previously unknown in Gyrfalcons, in which birds winter on sea ice far from land. During 2000–2004, data were collected from 48 Gyrfalcons tagged with satellite transmitters in three parts of Greenland: Thule (northwest), Kangerlussuaq (central-west) and Scoresbysund (central-east). Breeding home-range size for seven adult females varied from 140 to 1197 km2 and was 489 and 503 km2 for two adult males. Complete outward migrations from breeding to wintering areas were recorded for three individuals: an adult male which travelled 3137 km over a 38-day period (83 km⁄day) from northern Ellesmere Island to southern Greenland, an adult female which travelled 4234 km from Thule to ...